2022
DOI: 10.48550/arxiv.2204.07169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation of Low-mass Black Holes and Single Millisecond Pulsars in Globular Clusters

Kyle Kremer,
Claire S. Ye,
Fulya Kıroğlu
et al.

Abstract: Close encounters between neutron stars and main-sequence stars occur in globular clusters and may lead to various outcomes. Here we study encounters resulting in tidal disruption of the star. Using N -body models, we predict the typical stellar masses in these disruptions and the dependence of the event rate on host cluster properties. We find that tidal disruption events occur most frequently in core-collapsed globular clusters and that roughly 25% of the disrupted stars are merger products (i.e., blue stragg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…We have briefly mentioned one uncertainty in Section 2.3; that is, for massive and dense globular clusters, dynamical binary formation through NS-giant star collisions or tidal capture interactions may also contribute to a large portion of cluster MSPs (∼ 70% for massive and dense globular clusters similar to 47 Tucanae, see Ye et al 2022). Furthermore, observations have shown that core-collapsed globular clusters contain more isolated MSPs, which could be formed from tidal disruption events between a NS and a main sequence star (Kremer et al 2022). These effects combined together could contribute to a factor of a few in the number of MSPs formed in dense globular clusters, most of which are core-collapsed.…”
Section: Discussionmentioning
confidence: 99%
“…We have briefly mentioned one uncertainty in Section 2.3; that is, for massive and dense globular clusters, dynamical binary formation through NS-giant star collisions or tidal capture interactions may also contribute to a large portion of cluster MSPs (∼ 70% for massive and dense globular clusters similar to 47 Tucanae, see Ye et al 2022). Furthermore, observations have shown that core-collapsed globular clusters contain more isolated MSPs, which could be formed from tidal disruption events between a NS and a main sequence star (Kremer et al 2022). These effects combined together could contribute to a factor of a few in the number of MSPs formed in dense globular clusters, most of which are core-collapsed.…”
Section: Discussionmentioning
confidence: 99%